The Internet and Formations of Iranian American-ness : Next Generation Diaspora - Alinejad, Donya (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book explores how the children of Iranian immigrants in the US utilize the internet and develop digital identities. Taking Los Angeles-the long-time media and cultural center of Iranian diaspora-as its ethnographic field site, it investigates how various web platforms are embedded within the everyday social, cultural, and political lives of second generation Iranian Americans. Donya Alinejad unpacks contemporary diasporic belonging through her discussion of the digital mediation of race, memory, and long-distance engagement in the historic Iranian Green Movement. The book argues that web media practices have become integral to Iranian American identity formation for this generation, and introduces the notion of second-generation "digital styles" to explain how specific web applications afford new stylings of diaspora culture.
Keywords: Social sciences.; Ethnology -- Middle East.; Communication.; Mass media.; Social sciences in mass media.; Ethnicity.; Emigration and immigration.; elektronické knihy; electronic books